2019
DOI: 10.1021/acscentsci.9b01096
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Crystal Features of Thermostable Energetic Materials: Guidelines for Architecture of “Bridged” Compounds

Abstract: Extensive density functional theory (DFT) calculation and data analysis on molecular and crystal level features of 60 reported energetic materials (EMs) allowed us to define key descriptors that are characteristics of these compounds' thermostability. We see these descriptors as reminiscent of "Lipinski's rule of 5", which revolutionized the design of new orally active pharmaceutical molecules. The proposed descriptors for thermostable EMs are of a type of molecular design, location and type of the weakest bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(76 citation statements)
references
References 101 publications
4
72
0
Order By: Relevance
“…Covalent bond energies were calculated by the integrated value of crystal orbital Hamilton population (COHP) at the band energy using the HASEM package. [ 40,41 ]…”
Section: Methodsmentioning
confidence: 99%
“…Covalent bond energies were calculated by the integrated value of crystal orbital Hamilton population (COHP) at the band energy using the HASEM package. [ 40,41 ]…”
Section: Methodsmentioning
confidence: 99%
“…Here, Kissinger and Ozawa‐Doyle's methods are conducted based on the first exothermic peak temperatures ( T p ) measured at different heating rates of 5, 10, 15, 20 °C min −1 . As shown in Figure 4(d)‐4(f), under the heating rate of 5 °C min −1 , the decomposition of compound 6‐a commenced at 334.13 °C, and reached the peak at 347.91 °C incredibly, which is superior to most of heat‐resistant explosives such as TNT ( T d : 295 °C) [9], HNS ( T d : 318 °C) [6], bis(2,4,6‐trinitrophenyl) ether (BTNPE) ( T d : 256 °C) [1] and bis(2,4,6‐trinitrophenyl) (BTNPTE) ( T d : 310 °C) [1], but slightly lower than that of BPTAP ( T d : 366 °C). Compound 6‐b started to decompose at 324.5 °C, and arrived at 330.53 °C as its peak, which also surpasses those of TNT and HNS.…”
Section: Resultsmentioning
confidence: 96%
“…Additionally, the correlation between N‐heterocyclic skeleton and thermal stability as well as energy density has not been thoroughly referred [3–5]. Over the past few years, a series of thermally‐stable heterocyclic organic explosives emerged in large numbers, such as 1,3,4‐oxadiazole bridged trinitrophenyl derivatives [6], fused triazolo‐tetrazine [7], furazano[3,4‐b]pyrazine [8], bridging nitropyrazole derivatives with 1,3,4‐oxadiazole [9], 1,2,4‐oxadiazole [10], 1,2,5‐oxadiazole [11], 5,6‐fused bicycles [12], combination of 1,2,4‐oxadiazole derivatives with 1,2,5‐oxadiazole [13], polyaminotriazole derivatives and energetic salts [14–16], fused heterocyclic derivatives [17], etc. Heat‐resistant energetic materials for practical application that express significant features and properties including but not limited to: (1) their thermal stability should not be lower than 300 °C; (2) low cost and facile synthetic methods; (3) a lack of hypertoxic procedure or chemicals being utilized in its synthesis; (4) adequate solubility in most of solvents or at least high‐polar solvents for crystal modification and nano‐energetic materials for MEMS or detonator devices.…”
Section: Introductionmentioning
confidence: 99%
“…The properties of these compounds are showed in Table 14. Moreover, Li et al [124] synthesized the compound 106 with the procedure shown in Figure 34. This compound exhibited an excellent decomposition temperature (341 • C), high calculated detonation velocity of 8.52 km•s −1 , and detonation pressure of 30.6 GPa.…”
Section: Ring-bridged Bis(nitropyrazoles)mentioning
confidence: 99%
“…Afterwards, their group used a similar route to prepare bis(3,4-dinitro-1 H -pyrazol-1-yl)methane ( 89 ) and bis(3,5-dinitro-1 H -pyrazol-1-yl)methane ( 90 ) with high decomposition temperature and low sensitivities having capability as future energetic materials ( Table 13 ) [ 94 ]. Gozin et al [ 124 ] explored the possible influence factor of the thermostable property of explosives, and under the guidelines they proposed, they synthesized the compounds 91 and 92 with excellent thermal stability and moderate sensitivities shown in Figure 31 and Table 13 .…”
Section: Nitrated-bispyrazoles Based Compoundsmentioning
confidence: 99%